Hormesis, Cell Death, and Regenerative Medicine for Neurodegenerative Diseases - Guanghu Wang (SAGE Publishing, 2013)
Although the adult human brain has a small number of neural stem cells, they are insufficient to repair the damaged brain to achieve significant functional recovery for neurodegenerative diseases and stroke. Stem cell therapy, by either enhancing endogenous neurogenesis, or transplanting stem cells, has been regarded as a promising solution. However, the harsh environment of the diseased brain posts a severe threat to the survival and correct differentiation of those new stem cells. Hormesis (or preconditioning, stress adaptation) is an adaptation mechanism by which cells or organisms are potentiated to survive an otherwise lethal condition, such as the harsh oxidative stress in the stroke brain. Stem cells treated by low levels of chemical, physical, or pharmacological stimuli have been shown to survive better in the neurodegenerative brain. Thus combining hormesis and stem cell therapy might improve the outcome for treatment of these diseases. In addition, since the cell death patterns and their underlying molecular mechanism may vary in different neurodegenerative diseases, even in different progression stages of the same disease, it is essential to design a suitable and optimum hormetic strategy that is tailored to the individual patient.